2023
DOI: 10.1007/s00127-023-02479-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the prevalence of mental distress in East and West Germany over time: a hierarchical age-period-cohort analysis, 2006–2021

Abstract: Purpose Mental distress has become a major public health concern. Temporal trends in psychological distress are complex and depend on numerous factors. In this study, we examined age-period-cohort effects for mental distress including gender and German region over a 15 years’ time span. Methods Data on mental distress from ten cross-sectional surveys of the general German population, covering the years from 2006 to 2021, was used. Hierarchical age-period-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Similarly, younger participants, those with compulsory schooling only and unemployed participate reported higher distress and were more likely to reach potentially clinical levels of distress (caseness) [ 2 , 22 , 52 , 53 ]. While the effect of age might be explained by cognitive and emotional development but also differences in developmental tasks which are predominant in adolescence and young adulthood [ 54 ], others have found that a cohort effect related to political or global events might be important [ 55 ]. Regarding socio-economic characteristics, there is evidence based on a systematic review and meta-analyses that they influence psychological distress on various levels, such as experienced stress on the individual level or social comparisons on the neighborhood level [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, younger participants, those with compulsory schooling only and unemployed participate reported higher distress and were more likely to reach potentially clinical levels of distress (caseness) [ 2 , 22 , 52 , 53 ]. While the effect of age might be explained by cognitive and emotional development but also differences in developmental tasks which are predominant in adolescence and young adulthood [ 54 ], others have found that a cohort effect related to political or global events might be important [ 55 ]. Regarding socio-economic characteristics, there is evidence based on a systematic review and meta-analyses that they influence psychological distress on various levels, such as experienced stress on the individual level or social comparisons on the neighborhood level [ 56 ].…”
Section: Discussionmentioning
confidence: 99%